Gender Subversion in Angela Carter’s The Passion of New Eve - Bhandari, Sabindra Raj (AWADHARANA, 2022)
The main purpose of this article is to substantiate the issue of gender roles in Angela Carter's The Passion of New Eve. The main character “Evelyn” possesses the diverse sexual orientations both as Evelyn-male and Eve-female in the same body. Yet the issue remains on his/ her gender anxiety and identity crisis. The diverse sexual orientations blur the normative parameters of gender. That's why; the novel centralizes on crisis of gender anxiety and identity. The narrative exposes out by blending the dynamics of cultural and social myth. It limits modern-day society by subverting and examining the social formation of gender roles. Besides, this article exposes the dichotomy of heterosexism and homophobia that create segregation, prejudice, and fear in the society. To examine these issues, this article follows the paradigm of qualitative research with the theoretical lens of gender subversion and construction.